2008
DOI: 10.1158/1535-7163.mct-07-0337
|View full text |Cite
|
Sign up to set email alerts
|

LY2109761, a novel transforming growth factor β receptor type I and type II dual inhibitor, as a therapeutic approach to suppressing pancreatic cancer metastasis

Abstract: Most pancreatic cancer patients present with inoperable disease or develop metastases after surgery. Conventional therapies are usually ineffective in treating metastatic disease. It is evident that novel therapies remain to be developed. Transforming growth factor B (TGF-B) plays a key role in cancer metastasis, signaling through the TGF-B type I/II receptors (TBRI/II). We hypothesized that targeting TBRI/II kinase activity with the novel inhibitor LY2109761 would suppress pancreatic cancer metastatic process… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(206 citation statements)
references
References 36 publications
(35 reference statements)
6
196
0
Order By: Relevance
“…Taking advantage of a wide profile of kinase examination, we identified that LY2109761 selectively acts via a SMAD-dependent mechanism at different concentrations. This is also consistent with our previous study and with a study in pancreatic cancer cells [8,15]. In contrast to the pancreatic cancer cells, HCC cells seem to be more sensitive to LY2109761 treatment and show a five hundred fold higher sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taking advantage of a wide profile of kinase examination, we identified that LY2109761 selectively acts via a SMAD-dependent mechanism at different concentrations. This is also consistent with our previous study and with a study in pancreatic cancer cells [8,15]. In contrast to the pancreatic cancer cells, HCC cells seem to be more sensitive to LY2109761 treatment and show a five hundred fold higher sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…We used a low dosage, namely 50 mg/Kg once a day for twice a week, while Melisi et al used the same drug concentration twice a day for 5 days a week [15]. Unlike the mouse xenograft model, we used a chick embryo model and thus the difference in the animal model may explain our efficacy data on the kinetic of LY2109761.…”
Section: Discussionmentioning
confidence: 99%
“…Using an optimized dose and schedule, galunisertib demonstrated potent antitumor efficacy in multiple in vivo models, including human tumor xenografts and 4T1 syngenic mammary tumors. Our results are consistent with and expand the impact of prior reports that showed systemic treatment with monoclonal antibodies that target TGFβ ligands or the type II TGFβ receptor inhibit metastatic invasion of breast cancer cells in the 4T1 model [38][39], and previous reports on the impact of systemic treatment with small molecule inhibitors of TGFβ on in vivo xenograft and murine models of metastatic pancreatic cancer and glioblastoma [16][17][18]40]. In addition, our data further support prior reports showing the activity of the TGFβ pathway in promoting MDS [41].…”
Section: Discussionsupporting
confidence: 92%
“…Studies in genetically engineered mouse models and preclinical studies using TGFβ pathway antagonists support the pro-metastatic function of TGFβ, although this activity may depend on multiple factors, such as the nature of the tumor-initiating mutation, the precise mechanism of TGFβ inactivation, and the timing of TGFβ signaling [4,[12][13]16]. Small molecule TGFβRI inhibitors as well as antibodies directed to the type II receptor have been shown to block EMT and tumor cell migration in cancer cells [16][17][18]. In turn, TGFβ inhibition is currently being investigated as a treatment option in patients with advanced metastatic cancer [9,[19][20][21].…”
Section: Priority Research Papermentioning
confidence: 99%
“…Enhanced expression and activity of TGF-␤ has been reported in many models and human cases of PDA (5,30,(45)(46)(47)(48). To confirm that TGF-␤ signaling is critical for Fbln5 expression in pancreatic tumors, we examined Fbln5 levels in tumor tissue from KPC mice that had been treated with TGF-␤ inhibitors.…”
Section: Fbln5 Expression In Pancreaticmentioning
confidence: 99%